PERAN PENDIDIKAN ISLAM DALAM MENJAGA KESEHATAN MENTAL DI LINGKUNGAN SEKOLAH DI ERA SOCIETY 5.0 - Mutaqin, Ade Zaenul; Widi Krismawati Rosada (Program Studi Pendidikan Agama Islam, 2024)
The role of Islamic education in maintaining students' mental health in the school environment in the era of Society 5.0. The Society 5.0 era integrates advanced technology in various aspects of life, including education, which poses new challenges for students' mental health. Islamic education, with its spiritual and moral values, is believed to be able to provide solutions in overcoming this challenge. he research method used is qualitative with a case study approach. Data was collected through in depth interviews with teachers, students, and school staff in several schools that implement Islamic education. In addition, direct observation and analysis of documents are also carried out to enrich the data. The results of the study show that Islamic education has a significant role in maintaining students' mental health. The teachings on patience, dhikr, and Islamic moral values help students manage stress and emotions. The use of technology such as digital Al Quran applications and online discussion platforms allows the integration of Islamic values in students' daily lives, in accordance with the demands of the Society 5.0 era. School programs based on Islamic values, such as weekly recitation and counseling sessions, as well as teacher training in supporting students' mental health, have proven effective in creating a school environment that supports mental well being.